Peran Kepala Sekolah Menengah Kejuruan Dalam Menjamin Mutu Pendidikan Pada Masa Pandemi Covid-19 - Nandang Faturohman (Universitas Sarjanawiyata Tamansiswa, 2021)
Education is the right of all citizens guaranteed by law, not least during the Covid 19 pandemic. Students still have to get a proper education. This pandemic condition requires school principals to have the ability to manage the learning process so that the quality of education is guaranteed. This study aims to explore the leadership role of school principals, especially at the vocational secondary education level, in ensuring the quality of education during the COVID-19 pandemic. This research was conducted using the desk study method with a qualitative descriptive approach. The results showed that the leadership role of vocational high schools in ensuring the quality of education was carried out through 3 main things: LMS development, LMS use training, and online teacher performance assessment. This leadership practice can be categorized as a form of adaptive leadership that adapts to the conditions of the distance learning process that must be carried out during the COVID-19 pandemic.